Comparative Study of Fatty Acid Profiles in the Muscular Tissue (Longissimus Dorsis) of Bovines from Chile, Paraguay and Brazil - Silva-Serrano, J; Tomic-Stefanin, G; Osorio-Lira, F; Zamorano-Riquelme, M (Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA, 2019)
Per capita meat consumption in Chile is 89.1 kg per year in 2014, of which approximately 25 kg are beef. Some 50% of the beef consumed is imported as vacuum packaged meat from two species, Bos taurus, produced mainly in Chile, Argentina and Paraguay, and Bos indicus, which comes mainly from Brazil and Paraguay. The latter two countries account for the highest levels of beef imports in Chile. The objective of this investigation was to study and compare the fatty acid profiles of beef from Bos Taurus from Chile and Bos indicus from Paraguay and Brazil. Samples of vacuum packaged Longissimus dorsi muscle tissue were collected from private companies, two Chilean, three Paraguayan and two Brazilian. The fatty acid profiles were determined by GLC according to standardized regulations. There were differences in the fat profiles of the analyzed meats, mainly in the content of saturated and monounsaturated fatty acids. Brazilian and Paraguayan beef had similar fat compositions, with higher saturated fat content and lower monounsaturated fat content than the Chilean beef. The saturated and monounsaturated fat contents in the Chilean beef were similar. All the analyzed beef samples had a low content of trans and polyunsaturated fats. © 2019, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved.